WOMEN ADN EDUCATION IN CONTEMPORARY CHINA (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
The education of women in China has undergone an important process of changes throughout its thousands of history. Initially it was characterized by the predominance of a feudal society that forced the segregation in the private field, adopting a position of submission to man, and its learning was the result of the transmission of traditions and customs from mothers to daughters. From the 19th century and after the cultural contacts with Western societies, substantial changes have begun to take place, which promote the participation of women in the society and in the educational life. Since the establishment of the People's Republic of China, the development and the transformation of education have made great achievements, thanks to the Constitution ensures that women and men have the same right to education. Therefore, the old ideas of masculinity that still continue to generate with the stereotypes that in no way facilitate the development of women in the fields of education and occupation, and also the huge gap among different regions of Chinese education, are still the two major predicaments faced by Chinese women in education and gender discrimination.
Keywords: Education in China; Education for women; Diference of genders